Self-efficacy as a mediating variable of informal caregiver burden for dependent elderly. - Mata, Maria Augusta (2012)
The informal caregivers of dependent elders, plays a crucial role in maintaining the elderly in the family and community, but its work can be reflected negatively in their physical and emotional health, especially anxiety and depreSSion, loneliness, lack of free time, health effects and deterioration of the family economy. Several factors may be involved in its development, including stereotypes about the elderly, loneliness and self-efficacy of caregivers. In order to verify that the self-efficacy acts as a mediator of caregiver burden induced by the stereotypes and solitude, we drew up a cross-sectional and analytical study of 232 informal caregivers of dependent elderly in the district of Braganc;a - Portugal. It was found that loneliness has two indirect effects on burden, mediated through self-efficacy for a break and to controi negative thoughts about the act of caring. Stereotyping of biological decline has indirect effects mediated by self-efficacy to respond to inappropriate behavior of the person cared for and self-efficacy for controlling negative thoughts about the act of caring (via self-efficacy to respond to inappropriate behavior of the person cared for), hence there is a need for intervention with caregivers and the community as a whole. C022.2